A therapeutic HIV-1 vaccine reduces markers of systemic immune activation and latent infection in patients under highly active antiretroviral therapy. Issue 27 (2nd June 2020) - Pallikkuth, Suresh; Bolivar, Hector; Fletcher, Mary A.; Babic, Dunja Z.; De Armas, Lesley R.; Gupta, Sachin; Termini, James M.; Arheart, Kristopher L.; Stevenson, Mario; Tung, Frank Y.; Fischl, Margaret A.; Pahwa, Savita; et al.
Highlights: Immune assays were performed on HIV-1 patients receiving therapeutic vaccine HIVAX. HIVAX reduced the latent viral pool as measured by 2-LTR circles and total HIV-1 DNA. HIVAX reduced serum cytokines and cellular markers of systemic immune activation. HIVAX increased markers of activation on gag-specific CD4 + T cells. HIVAX may suppress immune activation and latent infection in HIV-1 infected patients. Abstract: HIV infection is characterized by chronic immune activation and the establishment of a pool of latently infected cells. Antiretroviral therapy (ART) can suppress viral load to undetectable levels in peripheral blood by standard measure, however immune activation/chronic inflammation and latent infection persist and affect quality of life. We have now shown that a novel therapeutic HIV vaccine consisting of replication-defective HIV (HIVAX), given in the context of viral suppression under ART, can reduce both immune activation/chronic inflammation and latent infection. Immune activation, as measured by percent of CD8 + HLA-DR + CD38 + T cells, approached levels of healthy controls at week 16 following vaccination. Reduced immune activation was accompanied by a reduction in pro-inflammatory cytokines and peripheral α4β7 + plasmacytoid DC (a marker of mucosal immune activation). Levels of both HIV-1 DNA and 2-LTR circles were reduced at week 16 following vaccination, suggesting HIVAX can impact HIV-1 latency and reduce viral replication. Surprisingly, reduced immune activation/chronic inflammation was accompanied by an increase in the percent of memory CD4 + T cells expressing markers PD-1 and TIM-3. In addition, evaluation of HIV-1 Gag-specific CD4 + T cells for expression of 96 T cell related genes pre- and post-therapy revealed increased expression of a number of genes involved in the regulation of immune activation, T cell activation, and antiviral responses. Overall this study provides evidence that vaccination with HIVAX in subjects under long term antiviral suppression can reduce immune activation/chronic inflammation and latent infection (Clinicaltrials.gov, identifier NCT01428596).